1988
DOI: 10.1182/blood.v71.5.1234.bloodjournal7151234
|View full text |Cite
|
Sign up to set email alerts
|

Epstein-Barr virus associated B cell lymphoproliferative disorders following bone marrow transplantation

Abstract: B cell lymphoproliferative disorders (BLPD) developed in eight patients following bone marrow transplantation (BMT) for leukemia (five patients) or immunodeficiency (three patients). Recipients of T depleted marrow from a mismatched donor were at particularly high risk of this complication. Six of 25 (24%) recipients of mismatched T depleted bone marrow developed BLPD. In contrast, none of 47 matched T depleted transplants, one of ten (10%) who received non-depleted marrow from an unrelated donor, and only one… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
100
0
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 184 publications
(104 citation statements)
references
References 55 publications
3
100
0
1
Order By: Relevance
“…Juvonen et al (37) reported an increased risk of PTLD in patients receiving ATG for treatment of steroid‐resistant acute GVHD. The use of ATG has been associated with a risk of PTLD in several other studies (5, 8, 13, 38–40). We use ATG in the conditioning regimen for patients with mismatched and unrelated donors and in spite of the fact that all patients in the study cohort who developed PTLD had received ATG, there was no significant impact of ATG or other forms of T‐cell medication on the risk of PTLD, presumably because ATG was also used in a high proportion of the patients who did not develop the disease.…”
Section: Discussionmentioning
confidence: 90%
“…Juvonen et al (37) reported an increased risk of PTLD in patients receiving ATG for treatment of steroid‐resistant acute GVHD. The use of ATG has been associated with a risk of PTLD in several other studies (5, 8, 13, 38–40). We use ATG in the conditioning regimen for patients with mismatched and unrelated donors and in spite of the fact that all patients in the study cohort who developed PTLD had received ATG, there was no significant impact of ATG or other forms of T‐cell medication on the risk of PTLD, presumably because ATG was also used in a high proportion of the patients who did not develop the disease.…”
Section: Discussionmentioning
confidence: 90%
“…On the basis of data from 234 centers reported to the International Bone Marrow Transplant Registry and the Fred Hutchinson Cancer Research Center between 1964 and 1992, the cumulative incidence of PTLD is 1.0±0.3% at 10 years after allo‐HSCT, and 58% of PTLD occurred within 1–5 months, and 82% occurred before 1 year (1). The incidence of PTLD is up to 24% after T‐cell‐depleted allo‐HSCT (21). The common risk factors of PTLD include HLA disparity, donor type (unrelated), T‐cell depletion of the graft, use of ATG in the preparative regimen, or GVHD prophylaxis and treatment in allo‐HSCT (1, 5).…”
Section: Discussionmentioning
confidence: 99%
“…The common risk factors of PTLD include HLA disparity, donor type (unrelated), T‐cell depletion of the graft, use of ATG in the preparative regimen, or GVHD prophylaxis and treatment in allo‐HSCT (1, 5). PTLD has rarely been reported after auto‐HSCT (21–24). PTLD usually occurs after transplantation of positively selected autologous CD34 + stem cells and in autologous transplant patients with autoimmune disease who use ATG (21, 23).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Posttransplant lymphoproliferative disorder (PTLD) is a serious complication of pharmacologic immunosuppression used routinely in solid organ and stem‐cell transplant patients. Up to 15% of transplant patients develop PTLD with a mortality rate of 40–70% (1–6). PTLD is often detected at a late stage when patients have a poor performance status and are suffering from side effects of their lymphoma.…”
Section: Introductionmentioning
confidence: 99%